ANALYSIS OF MATHEMATICAL CONNECTIONS ABILITY ON JUNIOR HIGH SCHOOL STUDENTS - Yoseph Sugi; Maria Agustina Kleden; Damianus D Samo (Universitas Ahmad Dahlan, 2021)
Mathematical connection is the ability to make connections to understanding mathematical concepts that are associated with contexts outside of mathematics. Various studies revealed that the students' mathematical connection is still low; therefore, this study aims to describe the difficulties of junior high school students in mathematical connection ability. This research is a descriptive qualitative study. The study sample was 52 students from a junior high school in East Flores Regency. The methods used in this study were tests, observations, and interviews. The study results showed that the mathematical connection ability based on the three indicators of connection ability tends to be below. Students did not understand concepts that had been studying; easy to forget concepts, principles and procedures; not used to use concepts, principles and procedures; assume mathematics has nothing to do with other sciences; not accustomed to applying mathematical concepts in everyday life; lack of understanding about the story